Hubungan Dukungan Keluarga Dengan Status Imunisasi Dasar Pada Anak Usia 10 bulan- 2 tahun Di Wilayah Kerja Puskesmas Totoli Kabupaten Majene” - Heriyati; Fajriani; Irwan, Muhammad (Nutrition Science and Health Research, 2024)
Immunization is the process of making a person immune or resistant to an infectious disease. Overall, Universal Child Immunization (ICU) states that Indonesia has the fourth highest prevalence in the world. Immunization has been proven to be one of the most important public health efforts. Through immunization, it can show great success because it is an effort to prevent infectious diseases. Immunization is influenced by several factors, including the mother's age, level of education, employment, number of children and family support. This research is a descriptive analytical study with a cross sectional approach which aims to see the relationship between family support and children's basic immunization status. The sample in this study was 84 children selected using a cluster random sampling technique with bivariate and univariate analysis using the chisquare test. Data were collected using a family support questionnaire and immunization completeness status. The results of the research show that there is a relationship between family support and basic immunization status for children in the Totoli health center working area with a p value of: 0.000. Family support in providing informational, appreciation, instrumental and emotional support has a big influence on maternal compliance in completing basic immunization status for children.